2021
DOI: 10.1038/s41431-021-00860-7
|View full text |Cite
|
Sign up to set email alerts
|

Balancing scientific interests and the rights of participants in designing a recall by genotype study

Abstract: Recall by genotype (RbG) studies aim to better understand the phenotypes that correspond to genetic variants of interest, by recruiting carriers of such variants for further phenotyping. RbG approaches pose major ethical and legal challenges related to the disclosure of possibly unwanted genetic information. The Cooperative Health Research in South Tyrol (CHRIS) study is a longitudinal cohort study based in South Tyrol, Italy. Demand has grown for CHRIS study participants to be enrolled in RbG studies, thus ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(170 reference statements)
1
7
0
Order By: Relevance
“…First, researchers should be attentive to what is important for participants and adequately address participant needs and views as partners. Second, as already highlighted in other empirical studies [19,20,[23][24][25], the context in RbG is essential, both in a sense previously identified [7] and at a societal level. Considering the specific disease under study and the meanings attached to it (e.g., possible stigma or discrimination) and the socio-economic conditions (including the access to health care) where the study is conducted would allow a deepened reflection on the societal implications of RbG studies and the extent to which specific research practices are transferrable to other contexts.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…First, researchers should be attentive to what is important for participants and adequately address participant needs and views as partners. Second, as already highlighted in other empirical studies [19,20,[23][24][25], the context in RbG is essential, both in a sense previously identified [7] and at a societal level. Considering the specific disease under study and the meanings attached to it (e.g., possible stigma or discrimination) and the socio-economic conditions (including the access to health care) where the study is conducted would allow a deepened reflection on the societal implications of RbG studies and the extent to which specific research practices are transferrable to other contexts.…”
Section: Discussionmentioning
confidence: 73%
“…The mother tongue of most residents in Val Venosta/Vinschgau is German [11]. Participant recruitment and the broader empirical RbG study have been described elsewhere [7,8] and summarized in Table 1.…”
Section: Study Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, the beginning of recall-by-genotype studies within the CHRIS study necessitated a change in the return of results policy. CHRIS participants were involved in this revision and empirical studies explored their views on the return of individual research results [ 17 ] and on the recall-by-genotype research approach [ 21 ]. The findings showed that participants want to make autonomous choices on the return of individual research result, and that a series of criteria affects their choice [ 17 ].…”
Section: The Chris Dynamic Consent Modelmentioning
confidence: 99%